Association Between Serum Ferritin Level and Type 2 Diabetes Mellitus: A Cross-Sectional Study (IAHS Medical Journal, 2026)
Background: Diabetes Mellitus is one of the most common chronic metabolic disorders affecting millions of people worldwide. Multiple factors appear to be involved in the pathogenesis of Type 2 Diabetes Mellitus (Type 2 DM). One of these factors may be iron overload. Increased serum ferritin concentrations in non-pathologic conditions, reflecting subclinical iron overload, have been reported to be associated with insulin resistance and an increased risk of Type 2 DM. The study aims to evaluate the association of serum ferritin level with type 2 diabetes mellitus patients.Materials and methods: This cross-sectional comparative study was conducted during the period from June 2022 to May 2023 in the Department of Biochemistry at Chittagong Medical College Hospital. The study consists of 110 study population out of which 55 were type 2 diabetic patients and 55 were non- diabetic subjects included by non probability purposive sampling. Fasting Blood Sugar (FBS), Postprandial Blood Sugar (PPBS), HbA1c, serum ferritin and Hb% were calculated following standard protocol. Statistical analysis was performed using SPSS v26.0 statistics.Results: The mean serum ferritin level of the diabetic patients was 146.45 ± 32.11µg/L, significantly higher (p